The way that you find this problem is to first find the slope, and then input one of your points into your equation to find b.
The slope-intercept form of a line is:
![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
, where m is the slope and b is the y-intercept.
To find the slope, you must use the following equation:
![\frac{y_{2}-y_{1}}{x_{2}-x_{1}}](https://tex.z-dn.net/?f=%5Cfrac%7By_%7B2%7D-y_%7B1%7D%7D%7Bx_%7B2%7D-x_%7B1%7D%7D)
In this equation, this would be equivalent to:
![\frac{-6-(-5)}{-7-(-1)}](https://tex.z-dn.net/?f=%5Cfrac%7B-6-%28-5%29%7D%7B-7-%28-1%29%7D)
which, when simplified, is
![\frac{1}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B6%7D)
. This is your slope.
To find the Y-intercept, you just plug all variables that you currently have solved for into the equation. You may use either point for the x and y variables, but you must use
![\frac{1}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B6%7D)
for the
m term.
![-6 = (\frac{1}{6})(-7) + b](https://tex.z-dn.net/?f=-6%20%3D%20%28%5Cfrac%7B1%7D%7B6%7D%29%28-7%29%20%2B%20b)
leads to
![-6 = \frac{-7}{6} +b](https://tex.z-dn.net/?f=-6%20%3D%20%5Cfrac%7B-7%7D%7B6%7D%20%2Bb)
which leads to
![\frac{-29}{6} = b](https://tex.z-dn.net/?f=%5Cfrac%7B-29%7D%7B6%7D%20%3D%20b)
. You have now solved for the y-intercept and aare ready to form your final equation.
The final equation is: